2014
DOI: 10.1002/zaac.201400014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conventional and Microwave Heating on SAPO‐5 Formation and Brønsted Acidic Properties

Abstract: Abstract. The hydrothermal crystallization of SAPO-5 molecular sieves with Si mole ratios in the range of 0.05 to 0.13 was performed by either conventional or microwave heating to compare the influence of these two techniques on the isomorphous substitution of phosphorus by silicon atoms in the aluminophosphate framework. An extensive characterization of the obtained silicoaluminophosphates by ICP-OES, SEM, XRD, TPDA, and MAS NMR spectroscopy indicated that conventional heating (drying oven) led to a better cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Parallel studies on SAPO-5 and SAPO-34 found differences in acidity, despite identical silicon loadings, depending on whether microwave or conventional heating was used. [98][99] Microwaved SAPO particles were much smaller, resulting in higher external surface area and mesopore pore volume, however, conventional samples contained a greater number of stronger acid sites. This was attributed to the differing silicon distributions of the two species, as conventional heating favoring isolated active sites (type II substitution, Figure 2), with a 1:1 ratio between silicon and protons.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Parallel studies on SAPO-5 and SAPO-34 found differences in acidity, despite identical silicon loadings, depending on whether microwave or conventional heating was used. [98][99] Microwaved SAPO particles were much smaller, resulting in higher external surface area and mesopore pore volume, however, conventional samples contained a greater number of stronger acid sites. This was attributed to the differing silicon distributions of the two species, as conventional heating favoring isolated active sites (type II substitution, Figure 2), with a 1:1 ratio between silicon and protons.…”
Section: Figurementioning
confidence: 99%
“…Microwave synthesis formed larger silicon islands, with fewer acid sites due to increased type III substitution, increasing the silicon-to-proton ratio (Figure ). , This suggests that rapid crystallization, from microwave heating, gives silicon less opportunity to enter the framework as isolated sites. , Thus, as crystallization occurs there are fewer available AlO 4 and PO 4 species, encouraging Si–O–Si bond formation and silicon islands. This shows that silicon distribution, and acidic properties (Figure ), can also be tailored by microwave heating time, with longer times required to form stronger acid sites, akin to those from conventional synthesis.…”
Section: Synthesis Of Sapo Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por su parte, el SAPO-5 presentó formas cúbicas de 3 micras de largo que se aglomeran en policristales de un tamaño entre 15 y 20 micras de espesor, (ver Fig. 4c), resultado que es coherente con otras investigaciones (Dang et al, 2014). Mediante esta técnica se encontró además composiciones puntuales de Al: 23.24; P: 28.15 y Si: 5.90, (%p/p), similares a las encontradas por análisis de AA las composiciones encontradas fueron de Al: 15.28; P: 20.03 y Si: 5.41, (%p/p).…”
Section: Caracterización De Los Sólidosunclassified